Chemical Composition of Millet-Based Infant Formula Supplemented with Treated Bambaranut Flour. - Nwabueze, T. U.; James, S.; Anuonye, J. C.; Kachiro, K. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2018)
Fermentation and sprouting have been shown to increase nutrient bioavailability and modify the functional properties of foods. Application of these methods in the preparation of infant foods and complementing cereals with legumes will address nutrient density and viscosity problems associated with infant foods. Infant foods were formulated from blends of treated bambaranut and pearl millet and chemical composition of the samples were studied. Millet and bambaranut were soaked separately in water and allowed to ferment for 48 hr at room temperature. While for sprouting, millet and bambaranut were soaked for 12 and 24 hr, respectively, at room temperature, and soaked seeds were separately sprouted for 48 hr. After fermentation and sprouting, the seeds were oven-dried and then milled into a flour of 0.6 mm size. The flours were formulated to six (A, B, C, D, E, and F) complementary diets. The results show that blending treated bambaranut with pearl millet significantly increased the protein, fibre, fat and ash content from 14.46, 0.68, 6.21 and 3.32% to 19.35, 1.21, 8.01 and 5.35% respectively; while, the moisture and carbohydrate contents were significantly reduced. In the same vein, blending treated bambaranut with pearl millet significantly increased all the amino acids composition of the blends. However, blending treated bambaranut with pearl millet increased the trypsin, hydrogen cyanide, oxalate and phytate contents; though, the values fall within the safe consumption limit. Hence, this study revealed that, blending treated bambaranut with pearl millet is beneficial in increasing the nutrient density of infant food.